Research advances on potential neurotoxicity of quantum dots. Issue 3 (13th September 2015) - Wu, Tianshu; Zhang, Ting; Chen, Yilu; Tang, Meng
Abstract: With rapid development of nanotechnology, quantum dots (QDs) as advanced nanotechnology products have been widely used in biological and biomedical studies, including neuroscience, due to their superior optical properties. In recent years, there has been intense concern regarding the toxicity of QDs with a growing number of studies. However, the knowledge of neurotoxic consequences of QDs applied in living organisms is lagging behind their development, while a potential risk of neurotoxicity arises if mass production of QDs leads to increased exposure and distribution in the nervous system. Owing to the quantum size effect of QDs, they are capable of crossing the blood–brain barrier or moving along neural pathways and entering the brain. Nevertheless, the interactions of QDs with cells and tissues in the central nervous system are not well understood. This review highlighted research advances on the neurotoxicity of QDs in the central nervous system, including oxidative stress injury, elevated cytoplasmic Ca 2+ levels and autophagy to damage in vitro neural cells, and impairments of synaptic transmission and plasticity as well as brain functions in tested animals, with the hope of throwing light on future research directions of QD neurotoxicity, which is a demanding topic that requires further exploration. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This review highlighted research advances on the neurotoxicity of QDs in the central nervous system, including oxidative stress injury, elevated cytoplasmic Ca2+ levels and autophagy to damage in vitro neural cells, and impairments of synaptic transmission and plasticity as well as brain functions in tested animals, with the hope of throwing light on future research directions of QD neurotoxicity, which is a demanding topic that requires further exploration.